Revealing the shallow soil structure of the Yigong Lake in the Tibetan Plateau using a portable distributed acoustic sensing interrogator - Yang, Jizhong; Zhou, Jian; Zhang, Heng; Xu, Tuanwei; Deng, Dimin; Geng, Jianhua (Frontiers in Earth Science, 2023)
The harsh and extreme environmental and near surface conditions of the Tibetan Plateau have limited the conventional electrical-based seismic instruments from obtaining high-quality seismic data through long-term and continuous observations, setting challenges for environmental seismology study and natural hazard monitoring in this area. Distributed acoustic sensing (DAS) is an emerging technique based on optical fiber communication and sensing. It provides a possible solution for subsurface imaging in extreme conditions at high spatiotemporal resolution by converting fiber-optic cables into dense seismic strainmeters. We deploy two survey lines with armored optical fiber cables in the Yigong Lake area, Southeastern Tibetan Plateau, to record ambient noise for a week. The DAS interrogator is specifically designed in a portable size with very low power consumption (25 W/h). Hence, we can use a 12V-DC battery for power supply to adjust the power limitation during the field recording. Ambient noise interferometry and multichannel analysis of surface waves are used to get 2D shear wave velocity profiles along the fiber paths. The results highlight the great potential of DAS for dynamic monitoring of the geological evolution of lakes and rivers in areas of extreme environments as in the Tibetan Plateau.